SciSpace for Finding Relevant Literature in English Language Education Contexts: A Technology Review - Kritandani, Weny; Putra, Angga Widitama; Mali, Yustinus Calvin Gai; Isharyanti, Neny (Indonesian Journal of English Language Studies (IJELS), 2024)
Writing a literature review part might be a challenging task for university students as they have to sit for some time to find recent literature that is closely relevant to their research topics. In that case, the authors spot the potential of utilizing SciSpace, Artificial Intelligence technology, to support the students in their literature review activities. In this study, the authors aim to review the potential benefits and challenges of using SciSpace to find recent literature relevant to students’ research topics, framed under the task engagement principles. To achieve that study goal, the authors used a recent technology review approach to do the review and conducted rigorous peer debriefing activities to ensure that the review results are credible and trustworthy. The review results showed the benefits of using SciSpace, which included fostering task authenticity, maintaining students’ interest, facilitating social interaction, supporting autonomy, and providing effective scaffolding. Meanwhile, the challenges of using SciSpace involved content accuracy and relevance, updating tailored content, handling complex queries and visuals, and offering context-specific feedback. Recommendations for maximizing the application's potential include improving content filtering, expanding interactive features, and providing specialized feedback. Future research agendas also are presented.